PENGARUH KINERJA PERUSAHAAN, RISIKO SISTEMATIS, DAN LEVERAGE TERHADAP RETURN SAHAM (Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Periode 2017-2019) - Tiaratama Sekar Endita; Fauzan Fauzan (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Stock return is one of the factors that motivate investors to invest and is also a reward for the courage of investors to take risks the investment he made. This study aims to determine the effect of company performance, systematic risk, and leverage to stock returns. Sampling in this study using purposive sampling and obtained a sample of 78 samples at the company manufacturing sector of the consumer goods industry listed on the IDX for the period 2017-2019. The data analysis technique used is multiple linear regression. Results the research shows that systematic risk has an effect on stock returns. While the company's performance and leverage do not effect on stock returns.